(untitled) (Journal of Obstetrics and Gynaecology of Eastern and Central Africa, 2024)
Background: Angiomyxomas are rare mesenchymal tumors. Aggressive angiomyxomas are distinguished from superficial angiomyxomas by their propensity for local recurrence and metastatic potential. Superficial angiomyxomas occur almost exclusively in women of reproductive age. Wide surgical resection is the treatment of choice. Case presentation: A 25-year-old para 1+1 presented with a mass on the vulva that had been increasing in size over one month. Examination revealed a mushroom-like, verrucous mass on the left labia majora with a raw surface measuring approximately 4 cm in diameter with a 2-cm stalk. It was easily bleeding on touch and slightly tender. Biopsies were taken, and histology revealed features of superficial angiomyxoma. The patient consented to wide excision of the vulval mass. The mass was excised together with approximately 1.5 cm skin margin around it and a 2 cm depth of the underlying fatty base. A final histological diagnosis of superficial angiomyxoma was made. The patient was followed up for three months with no recurrence. Conclusion: Superficial angiomyxomas are rare benign tumors of the subcutaneous tissue that occur almost exclusively in women of reproductive age. They present as slow-growing masses on the ear, trunk, and perineum. Wide surgical resection is the treatment of choice with adjuvant therapies, such as selective estrogen receptor modulators and gonadotropin hormone-releasing hormone agonists, also proving beneficial. Due to high rates of recurrence, long-term follow-up should be done for up to 15 years following primary resection.